IEEE INFOCOM 2003. Twenty-Second Annual Joint Conference of the IEEE Computer and Communications Societies (IEEE Cat. No.03CH37
DOI: 10.1109/infcom.2003.1208656
|View full text |Cite
|
Sign up to set email alerts
|

Design of light-tree based logical topologies for multicast streams in wavelength routed optical networks

Abstract: Abstract-In this paper, we formulate an optimization problem for the design of light-tree based logical topology in Wavelength Division Multiplexing (WDM) networks. The problem is comprised of two parts: (1) multicast routing and wavelength assignment of light-trees, and (2) the design of light-tree based logical topology for multicast streams. In the first part, we use Mixed Integer Linear Programming (MILP) to solve the optimal routing and wavelength assignment problem of light-trees with an end-to-end delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 18 publications
0
46
0
1
Order By: Relevance
“…Güç üleştirici çok pahalı olduğundan, ağın düğümlerinin sadece bir bölümünde kullanılır. Bu tip ağlar SeyrekDağılan (Sparse-Splitting) ağlar olarak adlandırılır [16].…”
Section: çOğa Gönderim (Multicast) Yapisiunclassified
“…Güç üleştirici çok pahalı olduğundan, ağın düğümlerinin sadece bir bölümünde kullanılır. Bu tip ağlar SeyrekDağılan (Sparse-Splitting) ağlar olarak adlandırılır [16].…”
Section: çOğa Gönderim (Multicast) Yapisiunclassified
“…In the first iteration, the Power Vector is initialized in step 1 with the least operational power values at the source nodes of the sessions under investigation 5 . In step 2, Q is constructed by populating it with all the outgoing links from these source nodes.…”
Section: Power Assignment (Pa) Modulementioning
confidence: 99%
“…However, it is more critical for All-Optical Multicasting (AOM) Service [2][3] as the optical signal in this case undergoes additional power loss. The source of this extra power loss is the splitting of the power strength of the incoming signal at the branching nodes of the multicast delivery structures (lighttrees [4] or light-forests [5]) into multiple output links. Power splitting is done in the optical domain using configurable passive optical splitters.…”
mentioning
confidence: 99%
“…All of these papers studied the multicast traffic grooming problem based on the lightpath wavelength channel model and approached the problem using integer linear programming (ILP) and heuristics. A more comprehensive study on this topic can be found in [11]. The authors proposed a unified ILP formula for static traffic, including unicast, multicast, and mixed traffic.…”
mentioning
confidence: 99%